CONSUMER ACCEPTANCE STUDIES OF SEAWEED SYRUP (Eucheuma cottonii ) WITH THE ADDITION OF A ROSELLA SOLUTION ( Hibiscus sabdariffa L. ) - Natama, Coki Randi; Sari, N. Ira; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The experiment was done in Novembre 2014. Research purpose was to determine theeffect the ussing of rosella solution at seaweed syrup on consumer acceptance. Rosella solution concentration used 0, 20, 40 and 60 ml. Parameters measured were consumer acceptance score, analysis of crude fiber, analysis of reducing sugar and total plate count. Based on research results, thatseaweedsyrup with addition ofa solution 60 ml rosellas which is thebesttreatmentto the characteristic redness appearance, the distinctive smell of rosellas, flavor of rosella was strong, and value of crude fiber 34,04%, value of reducing sugar 56,47% and value of total plate count 2,3 x 102.Keywords : seaweed, syrup, rosella, consumer acceptance